2003
DOI: 10.1002/app.13318
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of microwave‐assisted polymerization of ϵ‐caprolactone

Abstract: ABSTRACT:The kinetics of polymerization of ⑀-caprolactone (CL) in bulk was studied by irradiating with microwave of 350 W and frequency of 2.45 GHz with different cycle-heating periods (30 -50 s). The molecular weight distributions were determined as a function of reaction time by gel permeation chromatography. Because the temperature of the system continuously varied with reaction time, a model based on continuous distribution kinetics with time/temperature-dependent rate coefficients was proposed. To quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 41 publications
(34 reference statements)
0
28
0
4
Order By: Relevance
“…The kinetics of pure and zinc catalyzed ring opening polymerization of ε-caprolactone was also investigated in comparison to conventional heating syntheses and a model based on continuous distribution kinetics with time/temperature-dependent rate coefficients was proposed. From these coefficients the activation energies were calculated: while for pure thermal heating and catalyzed thermal heating the values were respectively 24.3 and 23.4 kcal/mol, the value found for catalyzed microwave heating was 5.7 kcal/mol, reflecting the observed increment in the polymerization rate (Sivalingam et al, 2004). Kinetic investigations were also performed comparing the rate constant for the stannous octoate catalyzed ROP of ε-CL under microwave conditions and conventional heating.…”
Section: Poly(ε-caprolactone)mentioning
confidence: 99%
“…The kinetics of pure and zinc catalyzed ring opening polymerization of ε-caprolactone was also investigated in comparison to conventional heating syntheses and a model based on continuous distribution kinetics with time/temperature-dependent rate coefficients was proposed. From these coefficients the activation energies were calculated: while for pure thermal heating and catalyzed thermal heating the values were respectively 24.3 and 23.4 kcal/mol, the value found for catalyzed microwave heating was 5.7 kcal/mol, reflecting the observed increment in the polymerization rate (Sivalingam et al, 2004). Kinetic investigations were also performed comparing the rate constant for the stannous octoate catalyzed ROP of ε-CL under microwave conditions and conventional heating.…”
Section: Poly(ε-caprolactone)mentioning
confidence: 99%
“…Zinccatalyzed polymerizations of e-caprolactone were reported by both Zhuo and co-workers [81] and by Madras and coworkers. [93] The latter used a multimodal microwave oven without controlling devices for temperature or pressure. To prevent overheating, the microwave irradiation was supplied in cycles of 40 or 50 s as it is commonly done with multimodal (domestic) microwaves ovens.…”
Section: Aliphatic Polyestersmentioning
confidence: 99%
“…28 This indicates so-called nonthermal effects, that the regrowth rate is increased with the assistance of the microwave field. Indeed, Sivalingam et al 29 and Fang et al 30 both found that the activation energy required for the bonding reaction by the microwave process is less than the thermal process, which leads to the recombination process being realized at lower temperature.…”
Section: B Non-thermal Effectsmentioning
confidence: 99%